Step
*
2
of Lemma
assert-bag-all
1. T : Type
2. eq : EqDecider(T)
3. p : T ⟶ 𝔹
4. bs : bag(T)
5. ↑bag-all(x.p[x];bs)
6. x : T
7. x ↓∈ bs
⊢ p[x] = tt
BY
{ Assert ⌜∀L:𝔹 List. ((↑reduce(λx,y. (x ∧b y);tt;L)) 
⇒ (∀b:𝔹. ((b ∈ L) 
⇒ b = tt)))⌝⋅ }
1
.....assertion..... 
1. T : Type
2. eq : EqDecider(T)
3. p : T ⟶ 𝔹
4. bs : bag(T)
5. ↑bag-all(x.p[x];bs)
6. x : T
7. x ↓∈ bs
⊢ ∀L:𝔹 List. ((↑reduce(λx,y. (x ∧b y);tt;L)) 
⇒ (∀b:𝔹. ((b ∈ L) 
⇒ b = tt)))
2
1. T : Type
2. eq : EqDecider(T)
3. p : T ⟶ 𝔹
4. bs : bag(T)
5. ↑bag-all(x.p[x];bs)
6. x : T
7. x ↓∈ bs
8. ∀L:𝔹 List. ((↑reduce(λx,y. (x ∧b y);tt;L)) 
⇒ (∀b:𝔹. ((b ∈ L) 
⇒ b = tt)))
⊢ p[x] = tt
Latex:
Latex:
1.  T  :  Type
2.  eq  :  EqDecider(T)
3.  p  :  T  {}\mrightarrow{}  \mBbbB{}
4.  bs  :  bag(T)
5.  \muparrow{}bag-all(x.p[x];bs)
6.  x  :  T
7.  x  \mdownarrow{}\mmember{}  bs
\mvdash{}  p[x]  =  tt
By
Latex:
Assert  \mkleeneopen{}\mforall{}L:\mBbbB{}  List.  ((\muparrow{}reduce(\mlambda{}x,y.  (x  \mwedge{}\msubb{}  y);tt;L))  {}\mRightarrow{}  (\mforall{}b:\mBbbB{}.  ((b  \mmember{}  L)  {}\mRightarrow{}  b  =  tt)))\mkleeneclose{}\mcdot{}
Home
Index